Numerical investigation of swirl-stabilized pulverized coal flames in air and oxy-fuel atmospheres by means of large eddy simulation coupled with tabulated chemistry. (1st March 2021) - Nicolai, H.; Wen, X.; Miranda, F.C.; Zabrodiec, D.; Massmeyer, A.; di Mare, F.; Dreizler, A.; Hasse, C.; Kneer, R.; Janicka, J.
Highlights: Development of an overall model based on large eddy simulation coupled with tabulated chemistry and detailed radiation modelling. Overall model is applied to a 60 kWth combustion chamber. Results are extensively validated against numerous measurements. The suitability of model to predict pulverized coal combustion in air and oxy-fuel atmospheres are demonstrated. Further analyses to investigate the differences of oxy-fuel atmospheres compared to air. Abstract: This paper investigates a self-sustained swirl-stabilized pulverized coal combustion chamber, specially designed to validate numerical models under atmospheric and oxy-fuel conditions. For this purpose, a comprehensive model, which accounts for both atmospheric and oxy-fuel conditions, is developed based on Large Eddy Simulation. To describe the turbulent gas-phase chemistry, a 4D Flamelet Generated Manifold based tabulated chemistry model is coupled with the artificially thickened flame approach and implemented in an Euler–Lagrange framework. The chemistry model is able to account for finite rate chemistry, heat losses, mixing devolatilization gases and char off-gases. Radiative heat transfer is included by solving the radiative transfer equation, applying the discrete ordinate method for angular discretization and a weighted sum of gray gas model for the spectral resolution, while particles are treated as gray. The simulation results from the combustion chamber are extensively validated against the available measurement data. Operating conditions with different atmospheres are investigated to validate the models' prediction accuracy for air and oxy-fuel atmospheres. The validation process is carried out using velocity fields, particle temperature measurements and the gas-species concentrations. Overall, the comparisons between simulations and measurements reveal a favorable agreement with only small differences near the burner opening. These results demonstrate the suitability of large-eddy simulation combined with tabulated chemistry for predicting the combustion of pulverized coal in conventional air and oxy-fuel atmospheres. Further analyses of the self-sustained coal flames are carried out; in particular, the influence of different atmospheres on the interaction of coal particles with the gas phase is studied.